ANALISIS PENGARUH LANGSUNG KUALITAS PELAYANAN, PERSEPSI NILAI PELANGGAN TERHADAP WORD OF MOUTH SERTA PENGARUH TIDAK LANGSUNG DENGAN KEPUASAN PELANGGAN SEBAGAI INTERVENING (Studi Pada RS Marzuki Mahdi Bogor) - Perdana, M. Rizky Putra; Soesanto, Harry (Diponegoro Journal of Management, 2016)
This study aims to analyze the influence of service quality and perceived value of the Word of Mouth by using customer satisfaction as a mediator variable (intervening) case study on service users of Marzuki Mahdi Hospital in Bogor. Service quality is a process that subjectively experienced by the customer, where the activities of production and consumption take place at the same time. Perceived value is the monetary value which is thought and is also a set of economic benefits, functional and psychological expected by the customer on a particular market offer. Customer satisfaction as the overall attitude towards the goods or services after the goods are consumed. Word of Mouth is a process of communication in the form of good recommendations provision either individually or in groups to a product or service that aims to provide information personally.Non-probability sampling is used for sample taking. Data were collected from 100 respondents which were selected using criteria of judgment that should have used the services of Marzuki Mahdi Hospital Bogor. Analysis method used a Likelihood Maximum Test with version 20.0 AMOS program.The result showed that the service quality and perceived value influence positively on Word of Mouth using customer satisfaction either as a mediator or not. While the service quality has the most impact on customer satisfaction followed by customer satisfaction on word of mouth, and perceived value on customer satisfaction.